2014
DOI: 10.4081/pmc.2014.104
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and prospective study of the effects of GH therapy on metabolic panel in children with GH deficiency

Abstract: a) At the time of diagnosis GHD children had a metabolic picture that was not different from non- GHD group; b) in children with severe GHD, the metabolic profile showed a trend towards at improvement after the initiation of replacement therapy with GH, with beneficial effects in terms of total cholesterol, LDL cholesterol and cardiovascular risk indices; c) GHD patients with unfavorable metabolic profile (high BMI and hypercholestorolemia) need a monitoring of glucose metabolism by periodical evaluations of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
3
0
4
Order By: Relevance
“…GH replacement therapy improved these symptoms in adult GHD (14). In children, serum lipid profiles, lean body mass and bone mineral content were improved by one or two years of GH replacement therapy (15, 16). We postulate GH replacement therapy is effective for metabolic abnormalities caused by GHD; however, the efficacy of GH replacement therapy for metabolic abnormalities in those who exhibit growth in the absence of GH needs to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…GH replacement therapy improved these symptoms in adult GHD (14). In children, serum lipid profiles, lean body mass and bone mineral content were improved by one or two years of GH replacement therapy (15, 16). We postulate GH replacement therapy is effective for metabolic abnormalities caused by GHD; however, the efficacy of GH replacement therapy for metabolic abnormalities in those who exhibit growth in the absence of GH needs to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the cardiovascular risk factors improved in children with GHD during the observation period according to previous studies [38][39][40] . These findings support the hypotheses that untreated GHD in childhood is associated with a deterioration in cardiovascular risk factors [6] and, in consequence, with an increased cardiovascular risk as measurable by cIMT in adults [14,15,17] and children [18,23] .…”
Section: Discussionmentioning
confidence: 91%
“…Radetti et al reported normalization of glucose tolerance in 5 out of 128 children who already presented impaired glucose tolerance before starting GHT ( 57 ), while unchanged glucose levels have been found in the majority of studies (14/21; 66.6%) ( 12 , 15 , 26 , 52 , 58 , 59 , 61 , 65 , 66 , 70 , 75 77 ).…”
Section: Resultsmentioning
confidence: 99%